Pengembangan Sistem Informasi Manajemen Yayasan Tuna Rungu: Studi Kasus Yayasan Pijar Mutiara Bangsa - Andriansyah, Mochamad Fachrul; Idris, Moh. (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
The Pijar Management Information System (SIM Pijar) is an information system designed to address management issues at the Pijar Mutiara Bangsa Foundation located in Klaten, Central Java. The primary problem involves manual processes for recording and archiving, which are considered inefficient and prone to errors, leading to potential data loss or damage. The implementation of SIM Pijar aims to mitigate these risks. This system is developed using HTML, CSS, PHP, and the Laravel and Bootstrap frameworks. Additionally, MySQL is used for data storage, following the Software Development Life Cycle (SDLC) Waterfall model. System testing is conducted using the User Acceptance Test (UAT) method, specifically black box testing, to evaluate the system's functionality. The testing results indicate that the system operates as designed and meets the functional requirements.